Managers, Management and Remote Work - A Competitive Advantage in the New Socio-Economic Context - Denisa Ligia Matei (Revista de Studii Financiare)
The pandemic has had a direct impact on the physical and mental health of millions of people around the world. In addition to the rapid spread of the virus and the high number of deaths, many people have experienced side effects such as fatigue, anxiety and depression due to social isolation and the uncertainty of the future. The managers had to face the challenges of both the business they were running and the teams they were targeting. In those teams, there were both anxious people, with personal challenges, as well as others that they had to keep trained. Some people often needed extra training to adapt to remote work. The COVID-19 pandemic has been one of the biggest challenges for managers and companies around the world. In this text, we will analyze how the pandemic has affected managerial leadership and the strategies adopted by companies to face this unprecedented crisis, but we will also analyze new open horizons and emerging opportunities, including as competitive advantages. In recent years, remote work has become increasingly popular, being adopted by more and more companies and workers around the world. This way of working offers numerous benefits, both for employees and employers. In this text, we will explore the advantages of remote work and how they can influence productivity, satisfaction and work-life balance.